2005
DOI: 10.2193/0091-7648(2005)33[688:mgrtho]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Mountain goat response to helicopter overflights in Alaska

Abstract: The number of helicopter flights used to gain access to backcountry has increased in recent years. Biologists, land managers, and the public have expressed concern about disturbance impacts to mountain goats (Oreamnos americanus) resulting from helicopter activity. We recorded behavioral responses of 122 groups of mountain goats from 347 helicopter overflights at 4 geographic areas in Alaska and analyzed responses in relation to distance and angle from helicopters to mountain goats, reproductive class, season,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
46
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 13 publications
(22 reference statements)
3
46
0
Order By: Relevance
“…Goldstein et al (2005) defined the awareness behaviour as the state where the goat stays with its head leaned toward some kind of stimulus. Quenette (1990) reported that animals standing aware are a sign of surveillance and that they stop what they are doing during their ongoing activity, raising their head and visually scanning the environment.…”
Section: Discussionmentioning
confidence: 99%
“…Goldstein et al (2005) defined the awareness behaviour as the state where the goat stays with its head leaned toward some kind of stimulus. Quenette (1990) reported that animals standing aware are a sign of surveillance and that they stop what they are doing during their ongoing activity, raising their head and visually scanning the environment.…”
Section: Discussionmentioning
confidence: 99%
“…increasing their movements and vigilant behaviour, decreasing foraging efficiency by shifting habitat and altering grouping patterns (Delaney et al 1999, Linklater & Cameron 2002, Patenaude et al 2002, Frid 2003, Southwell 2005, Tracey & Fleming 2007. Under certain conditions animals can become habituated to the disturbance (Miller & Gunn 1980, Stockwell et al1991, Hughes et al 2008) but the disturbance effects normally increase with increasing intensity of the harassment (Bayne et al 2000, Goldstein et al 2005. The proximity and the direction of the aircraft in relation to the animals influence the effect of the disturbance, with more severe reactions by the animals to direct approaches and short distances to the aircraft (Stockwell et al 1991, Frid 2003.…”
mentioning
confidence: 99%
“…The effects of helicopter disturbance on large mammals have been documented for ungulates, mostly from observing the animals during over-flights by helicopters in recreational or exploration traffic (Stockwell et al1991, Coˆte1 996) and during aerial surveys (Bleich et al 1990, 1994, Linklater & Cameron 2002. The experimental overflights show that ungulates react more severely to threatening approaches (more direct approaches or at a shorter distance; Frid 2003, Goldstein et al 2005, Tracey & Flemming 2007 but little is documented on the behaviour in large mammals in response to a helicopter directly approaching a single focal animal during research projects. The effects of direct helicopter approaches on large carnivores have not yet been reported even though routine helicopter approaches are used in many large carnivore projects.…”
mentioning
confidence: 99%
“…In some areas o f mountain goat range, including B.C., this disturbance is largely related to the expanding helicopter-supported recreation industry (Denton 2000, W ilson and Shackleton 2001, Festa-Bianchet and Cote 2008. Several studies have shown helicopter disturbance to cause short-term stress responses in mountain goats including fleeing, decreased foraging, and increased vigilance (Foster and Rahs 1983, Cote 1996, Goldstein et al 2005. These short-term impacts on behaviour could translate to consequences to movement rates, range use and ultimately survival and population productivity (W ilson andShackleton 2001, Festa-Bianchet andCote 2008).…”
Section: Acknowledgem Entsmentioning
confidence: 99%
“…Because there is often a lack o f standardization in their m easurem ent across the literature, for the purposes o f my thesis, short-term responses refer to the reactions o f animals to helicopters that occur directly following helicopter approaches and are verified by observer-based studies. The temporal scale o f reactions observed in these studies range from 15 minutes following disturbance (Goldstein et al 2005) to several hours following disturbance (Cote 1996). M edium-term responses are the responses to helicopter activity that are evident when observing the daily to seasonal behaviour patterns and habitat use o f animals that have been exposed to helicopter activity (e.g., changes in m ovem ent behaviour, temporary displacement).…”
Section: Acknowledgem Entsmentioning
confidence: 99%